Seroepidemiology of Chagas disease in at-risk individuals in Caraíbas, a city with high endemicity in Bahia State, Brazil - Tycha Bianca Sabaini Pavan; Deorlan Pereira Dias; Márcia Moraes Cangussú; Vilquenia Porto Pacheco Dutra; Daniel Dias Sampaio; Fred Luciano Neves Santos; Fred Luciano Neves Santos (Frontiers Media S.A., 2023)
IntroductionIn Brazil, an estimated 1.1 million people are infected with Trypanosoma cruzi, the causative agent of Chagas disease (CD). Despite the high number of cases, the estimated prevalence of infection per 100 inhabitants is low (0.03). However, the actual number of chronically infected individuals is still unknown. Therefore, we sought to determine the prevalence of chronic CD in at-risk individuals in Caraíbas (Bahia, Brazil) through active case finding.MethodsA total of 572 individuals living in rural or urban areas of Caraíbas were eligible for the study. A serum sample was collected from 226 individuals, and the diagnosis performed according to international guidelines.ResultsThe overall prevalence of anti-T. cruzi IgG was 4.42%. The median age of anti-T. cruzi IgG-positive individuals was 54.5 years, and the female-to-male ratio was 1.5:1. The prevalence of anti-T. cruzi IgG was similar in rural (4.29%) and urban areas (4.65%).DiscussionCompared with national estimates, we concluded that Caraíbas had a high prevalence for chronic CD and a high risk for persistent transmission. Through our study, it was possible to monitor individuals who were unaware of their clinical condition, thus improving their quality of life.